Reação de linhagens de soja à raça 3 d Heterodera glycines ichinohe - BRITO, CESIO HUMBERTO DE; Sediyama, Tuneo; Teixeira, Rita de Cássia; Paes, José Mauro Valente; Dias, Waldir Pereira (Revista Ceres, 2015)
-